P4-S3.09 The prevalence of Trichomonas vaginalis virus (TVV) in globally distributed Trichomonas vaginalis isolates. (10th July 2011) - Lezeau, L; Conrad, M; Gorman, A; Carlton, J
Abstract : Objective: Trichomonas vaginalis, a highly prevalent non-viral sexually transmitted infection, has been shown to be infected by a double-stranded RNA virus known as T vaginalis virus (TVV). The presence of this virus has been associated with increased trafficking of the immunogenic P270 to the surface of the parasite, and has therefore been hypothesised to be an important virulence factor in trichomoniasis. In the present study, we investigate the prevalence of TVV in globally distributed T vaginalis isolates and find an association between TVV infection and genetically distinct T vaginalis populations. Methods: 150 T vaginalis isolates from the USA, Mexico, Italy, Southern Africa, Papua New Guinea and Australia were screened for TVV infection by running total RNA extract on 1% agarose gels to detect the presence or absence of the diagnostic 4.5 kb dsRNA genome of the virus. The prevalence of TVV in genetically distinct T vaginalis phylotypes was compared using χ 2 tests. Results: TVV was found to be present in 37% of T vaginalis isolates. We find a difference in the prevalence of TVV infection between genetically distinct populations of parasites, with 3% of phylotype 1 isolates containing the virus vs 73% of phylotype 2 parasites (<0.001). Conclusions: TVV prevalence varies between T vaginalis phylotypes 1 and 2. This finding has implications suggesting that TVV is transmitted vertically among parasites, as more closely related T vaginalis strains are infected with TVV. Preliminary data also suggests that phylotype 2 parasites may show greater virulence, and further studies will be required in determining the role of TVV in this increased pathology.